Improving the relevance of randomised trials to primary care: a qualitative study investigating views towards pragmatic trials and the PRECIS-2 tool - Gordon Forbes; Kirsty Loudon; Megan Clinch; Stephanie J. C. Taylor; Shaun Treweek; Sandra Eldridge (Trials, 2019)
Abstract Background Pragmatic trials have been suggested as a way to improve the relevance of clinical trial results to practice. PRECIS-2 (Pragmatic Explanatory Continuum Indicator Summary-2) is a trial design tool which considers how pragmatic a trial is across a number of domains. It is not known whether a pragmatic approach to all PRECIS-2 domains leads to results being more relevant to primary care. The aim of this study was to investigate the views of people with influence on primary care practice towards the design of randomised trials, pragmatic approaches to trial design, and the PRECIS-2 domains. Methods We carried out semi-structured interviews with people who influence practice in primary care in the UK. A thematic analysis was undertaken using the framework approach. Results We conducted individual or small group interviews involving an elite sample of 17 individuals. We found that an exclusively pragmatic approach to randomised trials may not always make the results of trials more applicable to primary care. For example, it may be better to have less flexibility in the way interventions are delivered in randomised trials than in practice. In addition, an appropriate balance needs to be struck when thinking about levels of resourcing and the intensity of steps needed to improve adherence in a trial. Across other aspects of a trial’s design, for example the population and trial setting, a pragmatic approach was viewed as more appropriate. Conclusions To maximize the relevance of research directed at primary care, trials should be conducted with the same populations and settings that are found in primary care. Across other aspects of trials it is not always necessary to match the conditions found in practice.